Efektivitas Jenis Media Pada Penurunan Kandungan Polutan Air Limbah Laundry Menggunakan Moving Bed Biofilm Reactor - Dinda Putri Sriweni; Novirina Hendrasarie (Jurnal Serambi Engineering, 2025)
There is an increase in business activity in various fields, one of which is laundry services. This business can develop due to the increasing public demand for laundry services. The more laundry services are developed, the more waste is produced, which becomes an environmental problem. The development of this research idea is to use a variety of natural media (Bambo) and non-natural media (Kaldness K1 and Sponge) to determine the reduction of BOD5, COD, TSS and detergent. As a result, a waste water pollutant content test was carried out and the initial test results were BOD5 334 mg/l, COD 924 mg/l, TSS 142 mg/l and detergent 13.6 mg/l. The initial results show that the pollutant doesn't meet the quality standard according to the Governor's Regulation No. 72 of 2013, so it is necessary to carry out waste water treatment. The research results showed that Kaldness K1 media was the most effective in reducing the pollutant with BOD5 29 mg/l, COD 85 mg/l, TSS 48 mg/l and detergent 3.3 mg/l. Meanwhile, Bambo media has the lowest effective in reducing the pollutant BOD5 66 mg/l, COD 167 mg/l, TSS 59 mg/l and Detergent 4.7 mg/l. In conclusion, the MBBR method can reduce pollutants according to Governor Regulation No. 72 of 2013.